Analysis of the Influence of General Allocation Funds (DAU) and Regional Original Income (PAD) on Regional Expenditure Growth in Medan City in 2019-2023 - Siregar, Nur Wahidah Agustin; Yoandika, Ridho; Putri, Shabita; Khairani, Dinda; Chrisna, Heriyati (Lembaga Riset Mutiara Akbar, 2024)
This research aims to examine the influence of the General Allocation Fund (DAU) and Regional Original Income (PAD) on the growth of regional spending in Medan City during the 2019-2023 period. Regional development requires sufficient financing, and DAU and PAD are the two main sources of income which are very influential in regional financial planning. The method used in this research is descriptive and quantitative analysis with econometric models. Multiple linear regression tests were carried out to analyze the relationship between DAU, PAD and regional expenditure, after going through classic assumption tests such as normality, multicollinearity and heteroscedasticity tests. The research results show that although DAU and PAD contribute to regional spending, statistically their influence is not significant at the 95% confidence level. The regression model used has an R-square of 0.897, which shows that 89.7% of the variability in regional spending can be explained by independent variables. This research provides recommendations for designing fiscal policies that are more efficient in managing regional income sources to support sustainable development in Medan City.